Crimes and Society, How Do the Law Respond to Disruptive Conditions? (Law Research Review Quarterly, 2020)
Various crimes today are developing in a new direction, increasingly sophisticated, and modern (Juliana & Arifin, 2019). Even with motives that were never considered by humans in previous periods. The development of crime is also accelerating along with the development of society and information technology, especially in the era of disruption (Muthia & Arifin, 2019; Nurdiana & Arifin, 2019; Putri & Arifin, 2019; Arifin, 2020). This edition of the Law Research Review Quarterly explores a new nuance, with a fresh look and direction. This year's Law Research Review Quarterly Volume 6 Number 1 (February 2020) provides several articles relating to crime and various developments in society.